Analysis of Service Quality Policy on Patients Satisfaction at Benjeng Health Centers during COVID-19 Pandemic - Soni, Soni; Katmini, Katmini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Patient's assessment of the services of health workers is based on the patient's experience. The purpose of this study is to analyzeinfluence tangible, reliability, responsiveness, assuranceand empathy for the level of satisfaction of visitors to the Benjeng Health Center during the Covid 19 Pandemic.Subjects and Method: This was a cross sectional study with the focus of the research being directed at analyzing influence tangible, reliability, responsiveness, assuranceand empathy for the level of satisfaction of visitors to the Benjeng Health Center during the Covid 19 Pandemic. The total population is 2,000 respondents and a sample of 333 respondents taken using the simple random sampling. The data were described into number and percentage.Results: The findings showed that most of the respondents had a good tangible category as many as 171 respondents (51%). Most of the respondents have a good category of reliability as many as 178 respondents (53%). Most of the respondents have good category responsiviness as many as 165 respondents (50%). Most of the respondents have good assurance category as many as 184 respondents (55%). Most of the respondents have empathy in the good category as many as 174 respondents (52%). Most of the respondents have a satisfied category of satisfaction as many as 237 respondents (71%).influence tangible, reliability, responsiveness, assuranceand empathy for the satisfaction level of visitors to the Benjeng Health Center during the Covid 19 Pandemic with a magnitude of 79.1%.Conclusion: It is expected that respondents can provide constructive input and criticism so that the services provided can be in accordance with what is expected.Keywords: Quality of health service, satisfactionCorrespondence: Soni. Masters Program in Public Health, Strada Indonesian Institute of Health Sciences. Jl. Manila 37, Kediri, East Java 64133, Indonesia. Email: sonihamzah1@gmail.com. Mobile: +628121704715.Journal of Health Policy and Management (2023),08(01): 1-12 https://doi.org/10.26911/thejhpm.2023.08.01.01